Morphodynamic characteristics in a tidal inlet: San Blas, Argentina - Cuadrado, Diana Graciela (2011)
A tidal inlet on the Argentinean coast is studied. An integrated approach of combining detailed bathymetry survey, seabed sampling and tidal current measurements was used to characterize the tidal inlet morphodynamics. A Phase Measuring Bathymetric System (PMBS) “GeoSwath Plus” from GeoAcoustics Ltd. with centimetric precision and a mean swath coverage of 160 m, was used to recognize bedform morphologies and to determine bedform dynamics by comparison of successive surveys . Tidal velocities were recorded during a complete tidal cycle using an ADCP mounted on a ship operating at a frequency of 650 kHz. Maximum tidal currents, of the order of 2 m s−1 , exhibit different patterns across the channel. While maximum ebb currents dominate in the central and southern area of the channel, flood maximum currents dominate on the northern flank. The complex morphology of a dune field in an inlet and the resulting 3-D dune movement mechanism are also presented. In the middle of San Blas channel, a field with symmetrical large dunes (10–100 m in spacing) and very large dunes (N100 m in spacing) 4.5 to 5 m in height was found. Dune migration rates were measured by comparing two successive morphological maps of the field, reaching a rate up to 21 m year−1 toward the ocean. In contrast, the smaller dunes present on the northern border of the field migrate in an inward direction at a rate of 15.7 m year−1 .